RANCANG BANGUN APLIKASI E-COMMERCE DAN FORUM BUDIDAYA TANAMAN KEBUN BERBASIS ANDROID - Sutrianda Hardyan, Dea; Suhendri, Suhendri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Association of seed Breeders & Entrepreneurs (hppb) in bloom, farm facilities are business entities engaged in the sale of all plant seeds. This e-commerce application development refers to a manual system that is currently running. manual system that runs at this time based on consumers who come directly to the seller's place, in addition, the blooming of farm facilities has constraints ranging from the promotion process, transactions, to making sales reports that are still manual so that the sales process has not been well detailed, in the process of building e - This commerce uses data analysis techniques using the waterfall software development method, for the system data flow method using a structured method that uses DFD (Data Flow Diagram) to draw functional models and ERD (Entity Relationship Diagram) to draw data models, software development the system is java with a MySQL 5.0 database server. Based on the results of tests conducted by testing the alpha system using the black box and betha methods with questionnaires given to a number of respondents obtained the results that the overall system is running as expected.